Mixed Ionic–Electronic Conduction in NiFe2O4–Ce0.8Gd0.2O2−δ Nanocomposite Thin Films for Oxygen Separation. Issue 16 (1st August 2018) - Solís, Cecilia; Toldra‐Reig, Fidel; Balaguer, María; Somacescu, Simona; Garcia‐Fayos, Julio; Palafox, Elena; Serra, José M.
Abstract: NiFe2 O4 –Ce0.8 Gd0.2 O2− δ (NFO/CGO) nanocomposite thin films were prepared by simultaneously radio‐frequency (RF) magnetron sputtering of both NFO and CGO targets. The aim is the growth of a CO2 ‐stable composite layer that combines the electronic and ionic conduction of the separate NFO and the CGO phases for oxygen separation. The effect of the deposition temperature on the microstructure of the film was studied to obtain high‐quality composite thin films. The ratio of both phases was changed by applying different power to each ceramic target. The amount of each deposited phase as well as the different oxidation states of the nanocomposite constituents were analyzed by means of X‐ray photoelectron spectroscopy (XPS). The transport properties were studied by conductivity measurements as a function of temperature and p O2 . These analyses enabled (1) selection of the best deposition temperature (400 °C), (2) correlation of the p‐type electronic behavior of the NFO phase with the hole hopping between Ni 3+ –Ni 2+, and (3) following the conductivity behavior of the grown composite layer (prevailing ionic or electronic character) attained by varying the amount of each phase. The sputtered layer exhibited high ambipolar conduction and surfaceexchange activity. A 150 nm‐thick nanograined thin film was deposited on a 20 μm‐thick Ba0.5 Sr0.5 Co0.8 Fe0.2 O3− δ asymmetric membrane, resulting in up to 3.8 mL min −1 cm −2 O2 permeation at 1000 °C under CO2 atmosphere. Abstract : In sync for oxygen separation : NiFe2 O4 –Ce0.8 Gd0.2 O2− δ nanocomposite thin film is prepared by radio frequency magnetron co‐sputtering and used as a CO2 ‐stable composite layer for oxygen separation in which both electronic and ionic conduction are combined. Temperature and ratio of both phases is optimized to provide the best performance by applying a different power to each ceramic target. The sputtered layer exhibits high ambipolar conduction and surface exchange activity.